The Sustainability Marketing Mix for Thai Senior Tourism - Noo-urai, Nitchakarn; Jaroenwisan, Kaedsiri (International Journal of Social Sciences and Management, 2017)
This article was studied sustainability marketing mix strategy for Thai senior tourism. Collecting data through focus group discussion. The semi-structured interview used to collect data. The consequence of this research point out suitable product strategy for Thai senior tourism is the design of restroom with flush toilet with side-handrail and anti-slip floor material. In term of Price Strategy, sufficient accommodation cost is in range between 500 to 1,000 baht and entrance fee should not be over 100 baht. Place strategy is concentrated at accessible channel and attraction places information through internet, telephone, and word of mouth. Television media, used as Promotion Strategy, is most satisfactory media for Thai senior, which could be running period during 5:00 AM to 7:00 AM and 5:00 PM to 8:00 PM. In case of Participant strategy, traveling business is supposed to be emphasis on number of staff for this group of tourists that proper ration is a staff per three tourists. The Physical Evidence strategy is underline about decoration base on local identity and enough parking lot. And the process strategy is considered environmental prevention and protection which is use of clean energy or energy saving mechanic in accommodations. The packaging strategy is mention to package tour for senior tourist that provide conveniences and special services from expert staff. For programming strategy is religious festivals, traditional festivals, agriculture festivals, health festivals, etc. And partnership strategy is considered to highlight on business corporation to support Thai senior tourist services and build information center for senior tourists. Int. J. Soc. Sc. Manage. Vol. 4, Issue-2: 80-89